New Challenges to Health : the Threat of Virus Infection. - Smith, G. L. (Symposium of the Society for General Microbiology., 2001)
Viruses continually evolve and adapt, posing new threats to health. This book discusses the ecology of viruses with particular emphasis on the emergence of devastating haemorrhagic disease, and reviews the molecular and cell biological basis of the pathogenesis of several virus diseases. An introduction is given to the mathematical analysis of recurrent epidemic virus disease, such as measles. Neurological and psychological disease is discussed in relation to the pathological mechanisms that may underlie prion disease (such as new variant CJD) and to the possible virus involvement in human psy.